9(6x+8y-5z)=

Simple and best practice solution for 9(6x+8y-5z)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(6x+8y-5z)= equation:


Simplifying
9(6x + 8y + -5z) = 0
(6x * 9 + 8y * 9 + -5z * 9) = 0
(54x + 72y + -45z) = 0

Solving
54x + 72y + -45z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-72y' to each side of the equation.
54x + 72y + -72y + -45z = 0 + -72y

Combine like terms: 72y + -72y = 0
54x + 0 + -45z = 0 + -72y
54x + -45z = 0 + -72y
Remove the zero:
54x + -45z = -72y

Add '45z' to each side of the equation.
54x + -45z + 45z = -72y + 45z

Combine like terms: -45z + 45z = 0
54x + 0 = -72y + 45z
54x = -72y + 45z

Divide each side by '54'.
x = -1.333333333y + 0.8333333333z

Simplifying
x = -1.333333333y + 0.8333333333z

See similar equations:

| kx=logx | | 14t+24=10t+2t+30 | | 100000000x-1000000/-10000 | | (9x^2+5x^2-2)+(3x^2+3)= | | -3x^2+54=0 | | tn=3n+10 | | bt^2-(a+b)t+a=0 | | g(x)=4f(2x)-7 | | f(x)=2x+-12 | | h^3+2h^2-9h-18= | | 6+0.25x=0.8-5 | | X+0.3x=60 | | 4-7=3x+1 | | 6x-9x=1-7 | | X^2/2-5x-17 | | x^2+4x-16=-4 | | 5-(2x-1)=12-x | | 6/2x(3-4x)=2/3 | | 6y-1=7 | | 72pq/16q | | (3)^(-2)/(-2)^(-3) | | 1.6=-16x^2+64x | | -56x^2+14x+42=0 | | (5x^2-6x^4)+(7x^2+3x^4)=0 | | log[6](4x+5)=3 | | 21x^2+10x=0 | | 2+7k=65 | | 2x-12=-26 | | -5(p-2)+3p=6(p-4) | | R^2+16r-76=0 | | 6x2-12x-48/3x2-12x-36 | | 11p^2=-1 |

Equations solver categories